Development and investigation of multi-layered homo- and hetero-type DNA thin films. Issue 19 (3rd May 2018) - Arasu, Velu; Jeon, Sohee; Jeong, Jun-Ho; Park, Sung Ha
Abstract : Multi-layered DNA and CTMA-modified DNA thin films are fabricated and their novel physical characteristics are investigated. Abstract : DNA molecules have been studied for specific target applications because of their characteristics and modification abilities. Although the fabrication of 2D multi-layered DNA thin films has been demonstrated, limitations in their applications exist due to difficulties in controlling the layer thickness and fabricating hetero-stacking structures. Here, multi-layered homo- and hetero-type DNA and cetyltrimethyl-ammonium chloride (CTMA)-modified DNA thin films are fabricated via spin-coating and their physical characteristics are investigated. The thickness and the multilayer stacking influenced by the solvents, concentration, and spin-speed of the sample solution are also discussed. While DNA layers can be stacked either on a DNA or on a CTMA-modified DNA layer with the resulting thicknesses of approximately 100 and 300 nm, respectively, the CTMA-modified DNA layer cannot be stacked on a CTMA-modified DNA layer because of its solubility in the solvent. The optical and mechanical characteristics of the thin films indicate their dependency on film thickness. In addition, we fabricate the luminophore-embedded DNA and CTMA-DNA thin films with homo- and hetero-type layer stackings and measure the absorbance and photoluminescence spectra to show the feasibility in constructing functionalized multi-layered thin films. The homo- and hetero-type DNA layers and their revealed physical characteristics provide a platform for the construction of useful devices and sensors and a perspective for better understanding the applications in coating, transparent electrodes, transistors, and drug delivery.